Chronic Renal Failure As a Risk Factor For Cardiac Arrest in The Intensive Care Unit (ICU) - Ardi Pramono; Salma Azizah; Nur Chayati; Sagiran Sagiran (Universitas Malahayati Lampung, 2025)
ABSTRACT Chronic renal failure is a global problem, and there is a reciprocal relationship with cardiovascular disease. Cardiac arrest is one of the complications that can occur in patients with chronic renal failure. The study will look at whether chronic renal failure is a risk factor for cardiac arrest with chronic renal failure in patients in the ICU. This study used a cross-sectional analytical observational study design. The data taken was in the form of medical record data of patients with chronic renal failure in the ICU of PKU Muhammadiyah Gamping Hospital who experienced cardiac arrest without seeing the comorbidities of the disease. Total subjects amounted to 168 patients. To determine chronic renal failure as a risk factor for cardiac arrest, the data obtained were carried out bivariate regression test with a meaning of 0.05. Bivariate test results showed a p0.05 value, meaning chronic renal failure is not significantly a risk factor for cardiac arrest. Subjects with chronic renal failure had a relative risk (RR) of 1.27, which means they had a 1.27 times higher risk of cardiac arrest than patients without chronic renal failure. Chronic renal failure is not significantly a risk factor for cardiac arrest, but it has a greater risk of cardiac arrest than without chronic renal failure. Further research is needed, taking into account the underlying comorbid disease. Keywords: Chronic Renal Failure, Risk Factors, Cardiac Arrest, Intensive Care Unit (ICU)